The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/mi14030609
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Xanthan Gum Microspheres for the Sustained Release of Metformin Hydrochloride

Abstract: This work aimed to formulate xanthan gum microspheres for the encapsulation of metformin hydrochloride, according to the process of ionotropic gelation. The obtained microparticles, based on various fractions of xanthan gum (0.5–1.25), were subjected to different physico-chemical tests and a drug release study. Microspheres with an average size varying between 110.96 μm and 208.27 μm were obtained. Encapsulation efficiency reached 93.11% at a 1.25% biopolymer concentration. The swelling study showed a swelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The IR spectra of the tara gum samples showed a broad absorption band at 3393–3442 cm −1 due to the stretching frequency of the OH group [ 63 , 64 ]. The presence of –OH stretching could be attributable to sugars such as galactose and arabinose [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR spectra of the tara gum samples showed a broad absorption band at 3393–3442 cm −1 due to the stretching frequency of the OH group [ 63 , 64 ]. The presence of –OH stretching could be attributable to sugars such as galactose and arabinose [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of –OH stretching could be attributable to sugars such as galactose and arabinose [ 5 ]. The absorption band between 2924 and 2926 cm −1 is attributable to the stretching of the CH of the alkyl group [ 37 , 65 ], and those located between 1413 and 1424 cm −1 are due to the bending of the CH of the methyl group [ 64 , 65 ]. Likewise, the absorption bands located between 1633 and 1643 cm −1 are attributable to the asymmetric stretching of the carboxylate ion [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…This peak became narrower over time, particularly after the 720 W-6 min, however, the peak intensity increased compared to 960 and 1200 W, despite a reduction in the amount of water. The reduced intensity of this signal in treated XG samples at 960 and 1200 W could possibly be ascribed to OH group substitution (Yahoum et al, 2023). The broadening of this peak and its shift to a lower wavenumber with modification implies a gradual increase in the intermolecular hydrogen bonding between the molecules (Solo- de-Zaldívar et al, 2014).…”
Section: Dynamic Rheological Propertiesmentioning
confidence: 96%
“…Furthermore, it was recently reported that xanthan gum has a potential bloodsugar-lowering and stabilizing effect. This last particular property makes xanthan gum an excellent candidate for the administration of active antidiabetic substances [6,7] . Given that natural polymers are safe, biocompatible, and biodegradable, their contribution to the formulation of dosage forms is noteworthy.…”
Section: Introductionmentioning
confidence: 99%